Or Go Down in Flame : a Navigator's Death Over Schweinfurt - Wood, W. Raymond (Casemate, 2013)
""Though Anglo-American air power may be unrivaled in today's world, this was certainly not the case during Europe's last great war. Decades ago, when our airmen flew against Germany, horrific casualties resulted on both sides, and certain battles fought by the Allied powers can be termed nothing less than calamitous.""Black Thursday, "" the second Sc""